2015
DOI: 10.1002/2015gl065989
|View full text |Cite
|
Sign up to set email alerts
|

Cyclone Xaver seen by geodetic observations

Abstract: Cyclone Xaver pounded the North Sea on 5–6 December 2013 and reached its maximum in the German Bight the second day. Combined geodetic measurements from the SARAL/AltiKa satellite and from a local geodetic network detect cross‐shelf and alongshore variations and loading vertical deformation. The cross‐shelf root‐mean‐square differences between observations and predictions are 30 cm for surge height, 2 m for significant wave height, and 4 m/s for wind speed, with significant biases. The different wind forcing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…It is worth noting that such improvements in corrections should enable the full coastal exploitation of the data now flowing in from Ka-and SAR altimetry, and in particular the global SAR altimetry data now coming from Sentinel-3. This growing coastal altimetry field is going to support the monitoring of sea level in the coastal zone as well as other complementary applications such as the study of extreme events (storm surges-see for example Fenoglio-Marc et al 2015) and the validation of coastal wave models.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that such improvements in corrections should enable the full coastal exploitation of the data now flowing in from Ka-and SAR altimetry, and in particular the global SAR altimetry data now coming from Sentinel-3. This growing coastal altimetry field is going to support the monitoring of sea level in the coastal zone as well as other complementary applications such as the study of extreme events (storm surges-see for example Fenoglio-Marc et al 2015) and the validation of coastal wave models.…”
Section: Discussionmentioning
confidence: 99%
“…9) are observed. Fenoglio et al (2015) described the first surge maximum as a wind-induced maximum. They found that at Aberdeen and Lowestoft stations, the surge derived from the tide gauge records had only one maximum, reaching the eastern North Sea coastal areas (anticlockwise propagation) approximately 10 h later than Lowestoft (easternmost UK coast), causing the second storm surge maximum detected by the measurements in the German Bight.…”
Section: Sea Level and Wave-induced Forcingmentioning
confidence: 99%
“…Corrections for the ocean tide, the atmospheric inverse barometer effect and wind are not used. The storm surge is estimated by correcting the TWLE for the ocean tide given by the global ocean tide model GOT4.8 (Ray et al, 2011); see Fenoglio-Marc et al (2015) for more details.…”
Section: Observational Datamentioning
confidence: 99%
See 2 more Smart Citations